Initializing multi-stakeholder engagement in the context of Marine Protected Area management and capacity-building programmes: A Tun Mustapha Park case study - Boey, Sharlene S.; Wan Mohamad Ariffin, Wan Nur Syazana; Yang Amri, Affendi; Liew, Sandra; Lim, Voon-Ching; Fadzil, Kamal Solhaimi; Suhaimi, Julia; Syed Hussein, Muhammad Ali; Then, Amy Yee Hui; Goh, Hong Ching (Journal of Research Management and Governance, 2018)
As global trends in Marine Protected Area (MPA) management shift towards participatory co-governance, the importance of effective stakeholder engagement in its implementation stages warrant greater emphasis. This case study highlights key lessons learned from the employment of a mixture of focus group discussions (FGDs), interviews and reconnaissance surveys in a preliminary study-site visit to Tun Mustapha Park (TMP), Sabah, Malaysia, where our research team is undertaking a 4-year research and capacity-building project. We found that trust building, understanding the local culture and politics, and recognition of complex stakeholder dynamics were key elements to successful engagement, while identifying key decision-makers for follow-ups were crucial for on-going engagement. This paper presents insights into the types of information collected by our team, which would be useful among conservation practitioners who will be conducting similar engagement work in the future.